Pengaruh Feed Instagram Terhadap Citra Diri Mahasiswa Jurusan Ilmu Komunikasi Universitas Dharma Andalas - Dicky Syafhotra; Indria Flowerina (CV. ITTC INDONESIA, 2026)
The increasing use of Instagram among university students has positioned the Instagram feed as a strategic space for presenting identity and constructing self-image in the digital public sphere. As a permanent and curated visual display, the Instagram feed enables students to consciously manage impressions through visual appearance, theme consistency, captions, and audience responses. This study aims to examine whether there is a significant influence of Instagram feed on the self-image of Communication Studies students at Dharma Andalas University. This research employed a quantitative approach using a survey method. The population consisted of 188 Communication Studies students from the 2022–2025 cohorts, with a sample of 66 respondents determined using the Slovin formula and probability sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression, t-test, and coefficient of determination (R²). The results indicate that the Instagram feed has a positive and significant effect on students’ self-image, with a t-value of 12.640 and a significance level of p < 0.001. The regression equation obtained is Y = 7.739 + 0.836X, indicating that every one-unit increase in Instagram feed contributes to an increase of 0.836 in self-image. The coefficient of determination (R²) of 0.714 shows that, specifically for the sample group in this study, 71.4% of the variance in self-image is explained by the Instagram feed, while the remaining 28.6% is influenced by other factors outside this study. Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. These findings confirm that Instagram feed management plays a significant role in shaping students’ confidence, self-perception, and social evaluation in the digital era.